Blue-white variant of pigmented basal cell carcinoma - M. Turkmen; B. Gerceker Turk; I. Kilinc Karaarslan; B. Yaman; F. Ozdemir (Wolters Kluwer Medknow Publications, 2018)
Background: Basal cell carcinoma (BCC) is the most frequent of all skin cancers in the white population. The typical dermoscopic features of pigmented BCCs have been well known. In the literature a new dermoscopic pattern of BCC has been reported as "blue-white variant". Objective: In this study, we aimed to evaluate the blue-white variant of BCC's seen in our cases at our Dermato-oncology Unit. Methods: Patient files between the years 2003-2011 were searched for the cases with the histopathologic diagnosis of BCC. Among them, the cases that were compatible with the diagnosis of blue-white variant of BCC were determined. The morphological and clinical features of the lesions, dermoscopic images together with the histopathological slides were all evaluated. Results: Among 350 histopathologically proven BCCs, 3.1% of them showed diffuse blue-white areas, namely "the blue-white variant". On histopathological examination, typical aggregates of basaloid cells with nuclear atypia connected focally to the epidermis were observed. To our knowledge, this is the first research about the blue-white variant of pigmented BCC. Conclusion: The blue-white variant of pigmented BCC seems to be the most challenging type of BCC in the diagnosis for the clinician. Keywords: Basal cell carcinoma, Pigmented BCC, Dermoscopy, Blue-white variant, Melanoma, Noduler BCC